Literature Review: How and What is the Inflation Rate in Indonesia Today? What is the Government's Effort? - Dinda Sahira Rifly; Abd. Rasyid Syamsuri (Penerbit Merdeka Kreasi, 2023)
The literature review in this article aims to examine how and what is the current inflation rate in Indonesia and what efforts the government has made to follow up on things that are happening to related matters. The phenomenon of inflation in Indonesia is actually not solely a short-term phenomenon and one that occurs situationally, but like what is common in other developing countries, the inflation problem in Indonesia is more of a long-term inflation problem because there are still structural obstacles in the country's economy. Thus, it is not enough to improve the inflation problem in Indonesia by using monetary instruments alone, which are generally short-term, but also by making improvements in the real sector, namely with the main target of eliminating structural obstacles in the national economy. REFERENCE Adinugraha, H. H., Effendi, B., Rohmawati, I., & Khazani, A. N. (2021). Islamic Macroeconomics. NEM Publishers. Amrin. (2014). Forecasting Indonesia's inflation rate using neural network backpropagation based on the time series method. Nusa Mandiri Techno Journal. Central Statistics Agency. (2024). Development of the Consumer Price Index/Inflation. Jakarta: BPS. Bakti, T. D., Sumanjaya, R., & Hasution, S. H. (2010). Macroeconomics Lecturer. USUpress. Bank Indonesia. (2024). Inflation Report (Consumer Price Index) January 2024. Jakarta: BI Press. Bank Indonesia. (2024). Monetary Policy Review for the First Quarter of 2024. Jakarta: BI Press. Institute of Economics. (2023). The Impact of Inflation on the Welfare of the Indonesian People. Indonesian Economic Journal, 8(2), 145-160. Ismail, I., Misrah, M., & Soemitra, A. (2022). Bibliometric Analysis of Zakat Development in Indonesia During the Covid-19 Pandemic. Jurnal Ilmiah Ekonomi Islam, 8(2), 1357-1364. Soemitra, A., Ismal, R., Al-Butary, B., Ismail, I., Arpizal, A., & Harahap, R. A. (2021). MAQASID SHARIA IMPLEMENTATION IN MONETARY POLICY: A Literature Study. el-Amwal, 4(2). Hartini, D., & Utomo, Y. P. (2017). Analysis of the influence of inflation on economic growth in Indonesia. Journal of Development Economics. Ministry of Finance of the Republic of Indonesia. (2024). Indonesian Macroeconomic Analysis 2024. Jakarta: Ministry of Finance. Coordinating Ministry for Economic Affairs. (2024). National Inflation Control Strategy 2024. Jakarta: Coordinating Ministry for Political Affairs. Meita Nova Yanti Panjaitan, W. (2016). Influencing Factors Pella, B. J. J. S. (2024). The Effect of Food Security on Inflation, Especially Chili Products. Akubis: Journal of Accounting and Business, 9(1), 01-08. Rahmawati, D. D., & Riyanto, W. H. (2017). Analysis of the Effect of Bank Indonesia Certificate Interest Rate and Money Supply on the Inflation Rate in Indonesia for the Period 2006.1-2015.12 (Error Correction Model Approach). Journal of Economics JIE, 1(1), 60-74. Sri Handini, M. M., & Erwin Dyah Astawinetu, M. M. (2020). Portfolio theory and the Indonesian capital market. Scopindo Media Library. Sudiarti, S. (2022). PROBLEMATIKA HUKUM UMRAH KREDIT DALAM PANDANGAN IMAM SYAFII. CENDEKIA: Jurnal Studi Keislaman, 8(1), 63-80.